(untitled) (GYMNASIUM, 2009)
The performance is not born from an agglomeration of facts and happenings. It is a product of the effects caused by concerted actions of objective and subjective factors. Performance serves to self-realization and self-assertion, representing a goal of man since ancient times until present. Harnessing the full potential of individual sportsman in order to obtain the best results is the addiction to mental efficiency. Mental efficiency is based on self-knowledge and awareness of all the factors that can influence positively or not the process of preparation, on the way to achieve great performance.